2000
DOI: 10.1080/03093640008726533
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and movement control strategies in transtibial amputees

Abstract: This study was aimed at identifying changes in equilibrium and movement control strategies in trans-tibial amputees (TTA) related to both the biomechanical changes and the loss of afferent inflow. The coordinations between equilibrium and movement were studied in traumatical TTA and in controls during transition from bipedal to monopodal stance. TTA failed to perform the task in a high percentage of trials both when the sound and the prosthetic limb were supporting. Significant differences were also found betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 9 publications
1
47
1
4
Order By: Relevance
“…Their conclusion was that the required activity posed a very difficult task for most of the tested subjects. When standing on the prosthetic leg, the subjects need to maintain their balance solely by utilising hip and trunk strategies associated with double inverted pendulum models of stance where the centre of pressure excursions under the prosthetic foot are small due to the loss of the ankle joint (Viton et al, 2000). The important aspect of the results associated with the first outcome measure is that the majority of the subjects improved the duration of their standing after the treatment, which suggests that proper hip and trunk controlled balancing patterns were improved.…”
Section: Discussionmentioning
confidence: 99%
“…Their conclusion was that the required activity posed a very difficult task for most of the tested subjects. When standing on the prosthetic leg, the subjects need to maintain their balance solely by utilising hip and trunk strategies associated with double inverted pendulum models of stance where the centre of pressure excursions under the prosthetic foot are small due to the loss of the ankle joint (Viton et al, 2000). The important aspect of the results associated with the first outcome measure is that the majority of the subjects improved the duration of their standing after the treatment, which suggests that proper hip and trunk controlled balancing patterns were improved.…”
Section: Discussionmentioning
confidence: 99%
“…Afferent signals from proprioreceptors are reduced, which results in deterioration in balance 1 and limited function of selected muscles. 2 An amputee needs to adapt to their loss and learn new, or adjust to existing, movement patterns.…”
Section: Introductionmentioning
confidence: 99%
“…However, APRs are influenced by many factors, including anxiety [30], previous experience [31], attention [32], and joint position [33]. In transtibial prosthesis users, APRs differ from previous investigations involving muscular response [20][21][34][35] in that they do not allow preemptive postural adjustments in anticipation of a motor task, but are mediated by feedback mechanisms and not under volitional control [36][37]. Support-surface rotations (SSRs) have been used to investigate APRs in young nondisabled participants [29][30][38][39], as well as in older individuals [26] and those with total knee arthroplasty [40].…”
Section: Introductionmentioning
confidence: 98%
“…Studies of individuals with lower-limb amputation have linked falling with movement of the CoP in the anteroposterior direction [8] and in individuals without amputation with a movement of the CoP in mediolateral plane [17][18][19]. Other researchers have investigated CoP and muscular response to catching a falling object [20] or lifting a leg [21]. In addition to increased CoP excursion, these studies have demonstrated that prosthesis users have an alteration in automatic muscular responses compared with nondisabled individuals.…”
Section: Introductionmentioning
confidence: 99%